Review of monetary and credit policies in Belize 1976-1986 - Luben, Maydia (Institute of Social and Economic Research KingstonKN, 1986)
Briefly discusses the Belizean economy and describes the currency board system in operation prior to the establishment of the Monetary Authority in 1976. Assesses the impact of the Authority on the economy during the first three years of operations. Examines monetary policies pursued as part of an IMF Standby Arrangement since 1984. Discusses limitations to the effective execution of monetary policy.